Taḥlīl Akhṭā’ al-Aṣwāt al-ʿArabiyyah fī Mahārah al-Qirā’ah - Maratun Hamidah; Yelfi Dewi S (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This letter was submitted on the topic “Analyzing the Errors of Arabic Sounds in Reading Skill.” The object of this research is the students other than the department of Arabic language education at the state Islamic University of Bukittinggi are not able to pronounce the letters of the convergent sound, and then the department of Arabic language education at the state Islamic university of Bukittinggi, who are not able to pronounce all the alphabets. Then the type of this research is qualitative and descriptive. The data of this research are the result of the recording of students who read Arabic texts, and the data sources for this research are the students of the college of education and educational science, other than the department of teaching Arabic, using the snowball sampling technique. The research results show that the wrong form in reading Arabic texts is the changes in the sound of the analysis of errors. Analysis of student mistakes in the letter ظ becomes the letter ز and ج, the letter ط, becomes the letter ت, the letter ض becomes the letter د, the letter ث becomes the letter س, ش, and the letter ذ becomes the letter ز, ج, the letter ح becomes the letter ه, the letter ز becomes the letter س, the letter ع becomes the letter ء, and the letter ش becomes the letter س.هذه الرسالة قدمت بموضوع